Development of novel OCDMA codes for FTTH network / \c Thanaa Hussein Abd. - Hussein Abd, Thanaa (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2013)
The aim of this research is to develop a new family of codes for the spectral-amplitude coding (SAC) Optical Code Division Multiple Access (OCDMA) which can be superior to the performance of SAC-OCDMA systems.